2021
DOI: 10.3390/life12010038
|View full text |Cite
|
Sign up to set email alerts
|

Constituent Characteristics and Functional Properties of Passion Fruit Seed Extract

Abstract: The genus Passiflora L. is widely cultivated in tropical and subtropical regions. The major species, Passiflora edulis Sims, is known as ‘passion fruit’ and is widely used in processed foods as well as eaten raw. P. edulis fruits are eaten for their pulp together with the seeds; however, the seeds are often discarded when used in processed foods. P. edulis seeds contain a variety of nutrients and functional components, and their industrial use is desirable from the perspective of waste reduction. Previous stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 85 publications
0
18
0
1
Order By: Relevance
“…Buah markisa kaya akan vitamin C, senyawa polifenol (Viera, et al, 2022), serat pangan, dan mineral (Ramaiya, Bujang , & Zakaria, 2018). Berbagai penelitian juga telah membuktikan bahwa buah markisa memiliki manfaat sebagai antioksidan, antidiabetes, antihipertensi, dan antikanker (Kawakami, et al, 2022). Meski demikian, layaknya buah-buahan pada umumnya, markisa memiliki masa simpan yang relatif rendah serta tidak selalu tersedia sepanjang tahun (Paull & Chen, 2014).…”
Section: Pendahuluanunclassified
“…Buah markisa kaya akan vitamin C, senyawa polifenol (Viera, et al, 2022), serat pangan, dan mineral (Ramaiya, Bujang , & Zakaria, 2018). Berbagai penelitian juga telah membuktikan bahwa buah markisa memiliki manfaat sebagai antioksidan, antidiabetes, antihipertensi, dan antikanker (Kawakami, et al, 2022). Meski demikian, layaknya buah-buahan pada umumnya, markisa memiliki masa simpan yang relatif rendah serta tidak selalu tersedia sepanjang tahun (Paull & Chen, 2014).…”
Section: Pendahuluanunclassified
“…9 Some studies published in the literature show that Passiflora edulis seeds are also rich in bioactive compounds that present high antioxidant capacity 7 and anti-inflammatory, vasorelaxing, 4,[10][11][12] antitumor, antidiabetic and anti-adipogenic properties. [13][14][15] Vagula et al 16 identified phenolic compounds in Passiflora edulis seeds such as gallic acid (hydroxybenzoic acid) and chlorogenic acid (hydroxybenzoic acid).…”
Section: Introductionmentioning
confidence: 99%
“…Passion fruit (Passiflora edulis Sims), originated in South America, has been widely cultivated in tropical and subtropical regions worldwide because of its high pharmacological and edible value (Thokchom and Mandal 2017;Kawakami et al 2021). In China, passion fruit orchards are located mainly in the southern part of the country, in Guangxi, Fujiang, and Jinagxi provinces.…”
Section: Introductionmentioning
confidence: 99%